Petrogenesis of the ~2.77 Ga Monts de Cristal Complex, Gabon: Evidence for Direct Precipitation of Pt-arsenides from Basaltic Magma - Maier, W.; Rasmussen, Birger; Fletcher, Ian; Godel, B.; Barnes, S.; Fisher, L.; Yang, S.; Huhma, H.; Lahaye, Y. (Oxford University Press, 2015)
The Monts de Cristal Complex of Gabon consists of several igneous bodies interpreted to be remnants of a tectonically dismembered, >100 km long and 1–3 km wide, ultramafic–mafic intrusion emplaced at 2765–2775 Ma. It is the most significant mafic–ultramafic layered complex yet identified on the Congo Craton. The complex consists largely of orthopyroxenite cumulates, with less abundant olivine-orthopyroxenite and norite, and rare harzburgite and dunite. Mineral compositions (Fo ol 84, Mg# Opx 85, An plag 60–68, Cr/Fe chromite 1–1·45) and whole-rock data suggest that the parent magma was a low-Ti basalt containing approximately 10% MgO and 0·5% TiO2. Trace element and Rb–Sr and Sm–Nd isotope data indicate the presence of an enriched component, possibly derived from crustal contamination of a magma generated in the sub-lithospheric mantle. Most rocks show a highly unusual pattern of strong Pt enrichment (10–150 ppb) at low concentrations of Pd (1–15 ppb), Au (1–2 ppb), Cu (1–20 ppm), and S (<500 ppm), suggesting that unlike in most other PGE-rich intrusions globally, platinum in the Monts de Cristal Complex is not hosted in magmatic sulfides. Synchrotron X-ray fluorescence mapping has revealed the location of buried small Pt particles, most of which are associated with As. We propose that this constitutes some of the strongest evidence yet in support of magmatic crystallization of a Pt–As phase from S-undersaturated magma.